Bioassay Guided Fractionation of Phytocompounds from Bergenia ligulata: A synergistic approach to treat drug resistant bacterial and fungal pathogens - Rajan Rolta; Meghna Goyal; Saweta Sharma; Divya Bharaj; Deeksha Salaria; Navneet Kumar Upadhyay; Uma Ranjan Lal; Kamal Dev; Anuradha Sourirajan (Elsevier, 2022)
Bergenia ligulata Wall. Engl. is perennial herb used for the treatment urinary discharges, diseases of urinary bladder, dysentery, menorrhagia, splenic enlargement and heart diseases. The aim of the present study was to investigate the antimicrobial and synergistic potential of solvent fractions and major phytocompound of B. ligulata against bacterial and fungal pathogens. The antimicrobial and synergistic potential of the solvent fractions (Petroleum ether, chloroform, ethyl acetate, and remaining aqueous) of methanolic extract of B. ligulata rhizome and major phytocompound bergenin were investigated by agar well diffusion and broth microdilution method. Major Phytocompound bergenin was quantified in solvent fractions of B. ligulata by HPTLC and HP-LC method Molecular docking of bergenin was done by AutoDock vina with bacterial and fungal targets. Drug likeness and ADME screening was done with help of molinspiration and swissADME servers. Ethyl acetate sub-fraction of B. ligulata showed the highest antimicrobial activity against bacterial and fungal strains with zone of inhibition 13, 13, 14, 13 mm against Escherichia coli, Staphylococcus aureus, Candida albicans MTCC 277 and ATCC 90028 respectively. The MIC of ethyl acetate sub-fraction against E. coli, S. aureus, C. albicans MTCC 277 and ATCC 90028 was 31.25, 250, 62.5, 62.5 μg mg−1 respectively. Bergenin major phytocompound of B. ligulata also showed the antimicrobial activity with MIC 250 μg mg−1 against all the selected bacterial and fungal strains. Quantification of bergenin showed that ethyl-acetate sub fraction (17.6 μg mg−1 and 112 μg mg−1 measured through HPTLC and HPLC, respectively) is rich in bergenin content. The bergenin content recovered in ethyl acetate sub-fraction is 38.2%. Bergenin showed good interactions with bacterial and fungal targets and follows all parameters of drug likeness. Conclusions: : Solvent fractions of B. ligulata and major phytocompound Bergenin can be used as a bioenhancer of antibacterial and antifungal agents to treat drug resistant pathogens.